Hak Waris Anak Perempuan Tunggal Menurut Hukum Waris Adat Di Pulau Kisar Kabupaten Maluku Barat Daya - Mathias Kristison Maromon; La Ode Angga; Mahrita Aprilya Lakburlawal (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2022)
Women and men have the same position before the law regardless of gender, including the right to inherit. This research was carried out by referring to the type of normative legal research, or what is usually referred to as normative legal research or juridical where researchers will conduct a study of documents in the form of research conducted by examining literature sources and secondary data only, the type of research is descriptive analytical through an approach statutory and conceptual, guided by primary sources of legal material in the form of the 1945 Constitution of the Republic of Indonesia and the Civil Procedure Code as well as secondary and tertiary legal materials through the card system mechanism. Based on the research and presentation of the results and discussion, it was concluded that girls according to customary inheritance law on Kisar Island, especially in the community in Lebelau Village, North Kusar District, Southwest Maluku Regency, are not heirs, especially with regard to inheritance. This is influenced by the kinship system in adhered to by the people on Kisar Island in general, namely the patrilineal system so that sons become the heirs of priority according to customary law. The fulfillment of the inheritance rights of a daughter or only daughter in the family only includes inheritance that is the result of the income of the parents, where the fulfillment of these rights is very dependent on the wisdom of the parents.